Training effectiveness of eye tracking-based feedback at improving visual search skills. (1st January 2013) - Carroll, Meredith; Kokini, Christina; Moss, Jason
The goal of the present study was to explore the training effectiveness of a feedback method, which utilises eye tracking technology to support both expert demonstration and trainee assessment by measuring trainee scan data, diagnosing deficiencies, and providing feedback allowing a trainee to compare their scan to an expert scan. A training effectiveness evaluation (TEE) was performed to examine the ability of this method to improve individual search strategies and anomaly detection performance, both during training and in the field. The effects of the training were explored during virtual and practical application exercises within a Combat Hunter training course at the United States Marine Corps (USMC) School of Infantry (SOI). Of approximately 50 USMC participants, those who trained utilising eye tracking-based feedback showed significant improvements in search strategies compared to those who received traditional instructor-based feedback. This paper presents the TEE methodology and results and discusses implications of the findings.